1978
DOI: 10.1007/bf00406066
|View full text |Cite
|
Sign up to set email alerts
|

Arginine catabolism in Aphanocapsa 6308

Abstract: The catabolic products of arginine metabolism were observed in Aphanocapsa 6308, a unicellular cyanobacterium, by thin layer chromatography of growth media, by limiting growth conditions, and by enzymatic analysis. Of the organic, nitrogenous compounds examined, only arginine supported growth in CO2-free media. The excretion of ornithine at a concentration level greater than citrulline suggested the existence in Aphanocapsa 6308 of the arginine dihydrolase pathway which produced ornithine, CO2,NH4,+ adenosine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0

Year Published

1981
1981
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 17 publications
1
20
0
Order By: Relevance
“…(4,22,31,44,48). Arginine deiminase activity has also been reported for some strains of Anabaena sp., Aphanocapsa (Synechocystis) sp., and Nostoc sp.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…(4,22,31,44,48). Arginine deiminase activity has also been reported for some strains of Anabaena sp., Aphanocapsa (Synechocystis) sp., and Nostoc sp.…”
mentioning
confidence: 87%
“…Arginine deiminase activity has also been reported for some strains of Anabaena sp., Aphanocapsa (Synechocystis) sp., and Nostoc sp. (22,31,48). On the other hand, Synechococcus sp.…”
mentioning
confidence: 99%
“…However, Weathers et al (1978) demonstrated that cyanophycin could not be used as a carbon source by Aphanocapsa 6308.…”
Section: Cyanophycinmentioning
confidence: 99%
“…Amino acids like Arg, Asn, and Gln can be used as sources of nitrogen by a number of cyanobacteria (7), while Arg has been described to serve as a source of carbon for Synechocystis (Aphanocapsa) sp. strain PCC 6308 (29).…”
mentioning
confidence: 99%